The risk of suicide in a group of men hospitalized in forensic psychiatry departments - Fojcik, Joanna; Górski, Michał; Szulik, Justyna; Bogunia, Edyta; Skowronek, Rafał; Krzystanek, Marek (Frontiers in Psychiatry, 2026)
PurposeThe aim of this study was to determine the risk of suicidal behavior in patients who were involuntarily hospitalized in forensic psychiatry departments, taking into account demographic variables such as age, level of education and length of stay of patients in the department.Material and methodsThe study involved 112 patients of forensic psychiatry wards with a basic level of security, who completed an original questionnaire covering demographic data and the SBQ-R questionnaire on suicidal behavior.ResultsThe vast majority of patients studied were assigned to the low-risk category (96%), meaning they did not exhibit significant symptoms suggesting suicidal risk. Statistical analysis revealed no significant relationship between patient age and suicidal risk. Similarly, length of hospitalization had no significant effect on SBQ-R scores.ConclusionsMost patients scored low on the Suicide Risk Assessment Scale (SBQ-R), indicating a low level of suicidal ideation and tendencies.